2013
DOI: 10.1039/c3ta10433h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene–NiFe2O4 nanocomposites and their electrochemical capacitive behavior

Abstract: Reduced graphite oxide-NiFe 2 O 4 (RGO-NiFe 2 O 4 ) composites were synthesized by adding different amounts of NH 3 $H 2 O into a mixed aqueous solution of graphite oxide, Ni(NO 3 ) 2 and Fe(NO 3 ) 3 at room temperature. NH 3 $H 2 O was used to adjust the synthesis system's pH value. The morphology and the microstructure of the as-prepared composites were characterized by X-ray diffraction (XRD), BrunauerEmmett-Teller (BET) and transmission electron microscope (TEM) techniques. The structure characterizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(71 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…Recently, numerous works have been done on hybrid metal oxides-reduced graphite oxide (RGO), such as Mn 3 O 4 , Co 3 O 4 , NiO, Fe 2 O 3 , and NiAl-LDH [17][18][19][20][21][22]. However, spinel transition metal oxides (AB 2 O 4 ), with two metal elements provide the feasibility to tune the energy density and working voltage by varying the metal content, have less been developed [23][24][25] …”
mentioning
confidence: 99%
“…Recently, numerous works have been done on hybrid metal oxides-reduced graphite oxide (RGO), such as Mn 3 O 4 , Co 3 O 4 , NiO, Fe 2 O 3 , and NiAl-LDH [17][18][19][20][21][22]. However, spinel transition metal oxides (AB 2 O 4 ), with two metal elements provide the feasibility to tune the energy density and working voltage by varying the metal content, have less been developed [23][24][25] …”
mentioning
confidence: 99%
“…Complex oxides such as MnCo 2 O 4 [14,15], ZnMn 2 O 4 [16], NiCo 2 O 4 [17], NiFe 2 O 4 [18], and ZnCo 2 O 4 [19] etc., have been investigated as electrode materials for supercapacitors because of their excellent electrochemical performances. Among them, manganese-based oxide spinels are useful in many application fields (transport, telecommunication, medicine, and energy) due to their element abundance, low cost, and toxicity and electrical characteristics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that when the nanoparticles were deposited on graphene sheets they were uniformly distributed and entrapped inside the GO matrix forming an interconnected hybrid network. 29 The incorporation of nanoparticles into the graphene sheets prevents the agglomeration of nanoparticles and privileges the nucleation over growth and this combined effect led to the good particle density and monodispersity observed in the GO/NiF/ch nanocomposite. To investigate the stability of the particle, zeta potential measurements have been performed.…”
Section: Transmission Electron Microscopic (Tem) Studiesmentioning
confidence: 99%
“…However, until now, very few reports are available concerning the NiFe 2 O 4 graphene nanocomposites. 29,30 Chitosan, a natural polymer, is used to disperse nanomaterials due to its admirable properties such as non-toxicity, biodegradability, and good compatibility.…”
mentioning
confidence: 99%